Pulsed Nd:YAG laser welding of Ni-alloy Hastelloy C-276 foils - Ventrella, Vicente Afonso [UNESP]; Berretta, Jose Roberto; de Rossi, Wagner (Elsevier B.V., 2012)
In this study a pulsed Nd:YAG laser was used to join Hastelloy C-276 thin foil with 100 microns thickness. Pulse energy was varied from 1.0 to 2.25 J at small increments of 0.25 J with a 4 ms pulse duration. The macro and microstructures of the welds were analyzed by optical and electronic microscopy, tensile shear test and microhardness. Sound laser welds without discontinuities were obtained with 1.5 J pulse energy. Results indicate that using a precise control of the pulse energy, and so a control of the dilution rate, it is possible to weld Hastelloy C-276 thin foil by pulsed Nd: YAG laser. (C) 2012 Published by Elsevier B. V. Selection and/or review under responsibility of Bayerisches Laserzentrum GmbH
Keywords: Laser welding; Nd:YAG; Hastelloy C-276; Thin foil; Tensile shear test